The correlation of retinal neurodegeneration and brain degeneration in patients with Alzheimer’s disease using optical coherence tomography angiography and MRI - Zhao, Bingying; Yan, Yibing; Wu, Xingqi; Geng, Zhi; Wu, Yue; Xiao, Guixian; Wang, Lu; Zhou, Shanshan; Wei, Ling; Wang, Kai; Liao, Rongfeng (Frontiers in Aging Neuroscience, 2023)
Introduction: Pathological changes in Alzheimer’s disease can cause retina and optic nerve degeneration. The retinal changes are correlated with cognitive function. This study aimed to explore the relationship of retinal differences with neuroimaging in patients with Alzheimer’s disease, analyze the association of cognitive function with retinal structure and vascular density, and identify potential additional biomarkers for early diagnosis of Alzheimer’s disease. Method: We performed magnetic resonance imaging scans and neuropsychological assessments in 28 patients with mild Alzheimer’s disease and 28 healthy controls. Retinal structure and vascular density were evaluated by optical coherence tomography angiography (OCTA). Furthermore, we analyzed the correlation between neuroimaging and OCTA parameters in patients with mild Alzheimer’s disease with adjustment for age, gender, years of education, and hypertension. Results: In patients with mild Alzheimer’s disease, OCTA-detected retinal parameters were not significantly correlated with MRI-detected neuroimaging parameters after Bonferroni correction for multiple testing. Under multivariable analysis controlled for age, gender, years of education, and hypertension, the S-Hemi (0-3) sector of macular thickness was significantly associated with Mini-cog (β=0.583, P=0.002) with Bonferroni-corrected threshold at P<0.003. Conclusion: Our findings suggested decreased macular thickness might be associated with cognitive function in mild AD patients. However, the differences in retinal parameters didn’t correspond to MRI-detected parameters in this study. Whether OCTA can be used as a new detection method mirroring MRI for evaluating the effect of neuronal degeneration in patients with mild Alzheimer’s disease still needs to be investigated by more rigorous and larger studies in the future. Keywords: Alzheimer’s disease; cognitive; optical coherence tomography angiography; retinal structure; vascular density; MRI